Maternal outcome in preterm labor in a tertiary care hospital - Lewis, Preeti Frank; Kumari, Ayushi; Bavdekar, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To study the fetal and maternal outcome in preterm labor cases. Methods: It was Prospective, single centered, observational study. All women with preterm labor in the study period i.e. from September 2018 to March 2020 were included in the study i.e. 100 patients. Results: Out of 100 subjects, majority of mothers 65(65%) were in age group of 21-30 years followed by 23 (23%) in age group of ≤20 years. Majority 52 (52%) of study subjects were primigravida followed by 28 (28%) having parity 1. Only one case had parity 4. Majority 36 (36%) of study subjects were in lower class followed by 28 (28%) cases in lower middle class. 23 (23%) cases in middle class and 6 (6%) were in upper class. Maximum 61 (61%) cases were unbooked cases and rest 39 (39%) cases were booked. Out of 90 babies who were <2500 grams, maximum 57 (63.33%) were low birth weight (less than 2.5 kg) followed by 22 (24.44%) being VLBW babies. 10 cases were ≥2.5 kg, which are not LBW babies according to WHO Classification of low birth weight. Majority 34 (47.22%) stayed for 1-10 days followed by 17 (23.61%) babies for 11-20 days. Also 15 (20.83%) babies stayed for 21-30 days. Conclusions: Compared with term infants, preterm infants are at high risk of overall morbidity and mortality. Clinical suspicion, early detection and correction of risk factors, institutional delivery and good neonatal care back up facilities can improve the outcome of preterm labour and decrease the maternal complications as well.